MULTILEVEL INVERTER SIMULATION 9 LEVEL H-BRIDGE TOPOLOGY WITH HYSTERESIS CONTROL - Wisnu, Iqbal Fawzi; Andang, Asep; Rahayu, Andri Ulus (Teknik Elektro Universitas Siliwangi, 2023)
Inverter is an electronic circuit to convert DC power source into AC. In general, the inverter will produce a relatively large Total Harmonic Distortion (THD) value so that it will result in damage to electronic devices, to minimize this, a multilevel inverter is made which can reduce the THD value by increasing the level using the switching method. In this research a 9-level cascaded H-Bridge topology cascaded H-Bridge topology simulation is designed to identify the output of this multilevel inverter. The addition of R, RL, RC, RLC, and induction motor loads affects the THD value. To calculate THD, we use Fast Fourier Transfer (FFT) on MATLAB Simulink. The no-load test results produced a THDv of 13.90%. In the R load test the resulting THDv and THDi values were 13.91%. In the RL load test it produces a THDv value of 13.91%, and a THDi of 0.2% to 0.12%. In the RC load test it produces a THDv value of 13.91% to 13.85%, and a THDi of 15.55% to 70.53%. The RLC load test produced a THDv value of 13.91% and the lowest THDi was 0.06%. In the load test, the induction motor produces a THDv value of 13.91% to 13.92%, and a THDi of 0.88% to 0.25%.